2020
DOI: 10.3389/fneur.2020.00137
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Altered in Mild Cognitive Impairment Compared With Normal Cognition in Sporadic Parkinson's Disease

Abstract: Background and Aim: Gut bacteria play an important role in the pathogenesis of Parkinson's disease (PD). However, the alteration of fecal microbiota in PD with cognitive impairment remains unexplored. This study aimed to explore whether the gut microbiota of patients with PD having mild cognitive impairment (PD-MCI) were different from those with PD having normal cognition (PD-NC) and from healthy controls (HC). Also, the study probed the association between altered gut microbiota and cognitive ability in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 27 publications
5
124
4
Order By: Relevance
“…Further studies on members within this genus in anti-LGI1 encephalitis are needed. Recent studies have reported that some bacteria are associated with not only the onset of diseases but also with the certain clinical symptoms (40)(41)(42). Given the fact that the Sphingomonas genera increased in both anti-LGI1 encephalitis and Parkinson's disease, we made a bold assumption that the Sphingomonas may link to the extrapyramidal symptoms or even the pathomechanisms of FBDS.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies on members within this genus in anti-LGI1 encephalitis are needed. Recent studies have reported that some bacteria are associated with not only the onset of diseases but also with the certain clinical symptoms (40)(41)(42). Given the fact that the Sphingomonas genera increased in both anti-LGI1 encephalitis and Parkinson's disease, we made a bold assumption that the Sphingomonas may link to the extrapyramidal symptoms or even the pathomechanisms of FBDS.…”
Section: Discussionmentioning
confidence: 97%
“…This provides support for our hypothesis that gut-dysbiosis is associated with an altered neuroinflammatory response that increases susceptibility to various clinical features, including depression and anxiety. Indeed, evidence is mounting that gut-dysbiosis is associated with a wide-range of symptoms in PD, including motor symptom severity, REM behavior sleep disorder and cognitive impairment [4] , [33] , [34] , [35] . However, findings of the association between non-motor symptoms, inflammation and dysbiosis have been correlational, and caution against causal assumptions are appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has hinted that GM may be associated with hypertension [ 32 , 42 – 44 ]. In this study, higher abundances of TM7 and TM7-3 were found in HTNCI patients than in HTNnCI patients.…”
Section: Discussionmentioning
confidence: 99%